Voltammetric oxidation of solution and solid phases of salts of [V(CO)6]- in aqueous (electrolyte) media - Bond, Alan M.; Colton, Ray; Mahon, Peter J.; Snook, Graeme A.; Tan, Wee T. (American Chemical Societyservice@acs.org, 1998)
In the absence of water and oxygen the solution phase voltammetry of [V(CO)6]- in organic solvents exhibits an extremely well-defined, reversible, one-electron redox couple [V(CO)6]- ⇋ V(CO)6 + e-; ET1/2 = -0.35 V versus the ferrocenium/ferrocene (Fc+/Fc) couple, where ET1/2 is the reversible half-wave potential. Addition of water or oxygen causes the response to become irreversible, but all components remain soluble. Simulations of the solution-phase voltammetry in acetone/water mixtures (no oxygen present) are consistent with the mechanism V(CO)6 + H2O → V(CO)5(H2O) + CO. The sodium diglyme stabilized [V(CO)6]- salt ([Na-(diglyme)2][V(CO)6]) is slightly soluble in water without decomposition. In contrast, solid V(CO)6 is insoluble in water, but reacts so slowly with it that solid state voltammetry of the [V(CO)6]0/- system is possible in aqueous media. Oxidation of [Na(diglyme)2][V(CO)6] dissolved in water (electrolyte) media gives insoluble V(CO)6, which precipitates onto platinum, gold, or carbon electrodes. Cyclic voltammetry, electrochemical quartz crystal microbalance, chronocoulometric, and electron microscopy studies show that V(CO)6 is precipitated as lumps of solid rather than as uniform layers. Voltammetric studies on [Na(diglyme)2][V(CO)6] mechanically attached to electrodes that are then placed into aqueous (electrolyte) media show distinct relationships to the voltammetry of dissolved [Na(diglyme)2][V(CO)6]. However, in this case, ion exchange with the electrolyte cations and gradual dissolution of the mechanically attached solid occurs. The potentials are independent of the electrolyte anions, but change considerably (>600 mV) with the electrolyte cation. In the cases of the tetraalkylammonium cations (NR4+), the potentials are correlated with the solubility products of [NR4][V(CO)6]. Equations are presented relating the potentials of the processes and the concentration of the cations and the solubility products of the salts.